Increasing Vocabulary Mastery of The First Year Students of Smp Negeri 3 Pamboang Through Concept Mapping Strategy - nurfitri; Abdul Haris Sunubi (Inspiring: English Education Journal, 2018)
This study is to see increasing vocabulary mastery of the first-year students of SMP Negeri 3 Pamboang through concept mapping strategy. The problems in this research are using concept mapping strategy able to increase students’ vocabulary in the first-year students of SMP Negeri 3 Pamboang. This study aimed to know the students' responses toward concept mapping strategy in increasing vocabulary and to find out whether there is a significant increase of students’ vocabulary achievement as a result of using concept mapping strategy. This study employed a quantitative research design which is a case study using pre-experimental design which applied (one group pre-test and post-test design). The study found out that there was an improvement of the students’ vocabulary mastery after giving the learning process by using concept mapping strategy. It can be concluded that the students’vocabulary mastery is significantly better after getting the treatment. This study also provides a set of recommendation to avoid overlapped researches in education technology.